Nickel in tropical legumes: growth responses, impacts on morphophysiology, and sustainability perspectives - Ferreira, Tassia Caroline [UNESP] (UNESP, 2025)
This thesis investigates the physiological and biochemical responses of tropical legumes from the Fabaceae family to stress induced by nickel, a potentially toxic element present in soil at elevated concentrations. The study is structured around three chapters that explore different aspects of these species' reactions to nickel. The first chapter, concerning the scoping review, was conducted following the PRISMA protocol and aimed to map the Fabaceae species studied, the methodologies employed, and the physiological markers analyzed in peer-reviewed articles published between 2013 and 2022. The results highlight Glycine max as the most extensively studied species, while most research focuses on biotic stress, fertilization, and toxicity. However, physiological aspects such as nodules, biological nitrogen fixation, carbon metabolism, and gas exchange are underrepresented in the literature. The second chapter focuses on changes in biomass, nickel accumulation, and morphophysiological aspects of C. mucunoides and C. ensiformis in contaminated soils, revealing that C. ensiformis shows higher tolerance to nickel, with anatomical adaptations that allow greater accumulation of the element. The third chapter examines alterations in the leaf structure of these species under nickel stress, using morphological and biochemical analyses to understand how plants maintain cellular stability and physiological functioning under stress. The study showed that C. mucunoides exhibits higher sensitivity, with significant changes in water use efficiency and pigment activity, while C. ensiformis demonstrates greater resistance, maintaining gas exchange even under elevated stress conditions. The findings contribute to the understanding of the acclimatization strategies of tropical legumes to potentially toxic elements, with implications for the use of these species in phytoremediation programs and the restoration of degraded soils.

A presente tese investiga as respostas fisiológicas e bioquímicas de leguminosas tropicais da família Fabaceae ao estresse provocado pelo níquel, um elemento potencialmente tóxico presente no solo em concentrações elevadas. O estudo foi desenvolvido a partir de três capítulos que exploram diferentes aspectos das reações dessas espécies ao níquel. O primeiro capítulo, referente à revisão de escopo, foi conduzido seguindo o protocolo PRISMA e teve como objetivo mapear as espécies da família Fabaceae estudadas, as metodologias empregadas e os marcadores fisiológicos analisados em artigos revisados por pares publicados entre 2013 e 2022. Os resultados destacam Glycine max como a espécie mais investigada, enquanto a maioria dos estudos se concentra em estresses bióticos, fertilização e toxicidade. No entanto, aspectos fisiológicos como nódulos, fixação biológica de nitrogênio, metabolismo do carbono e trocas gasosas são sub-representados na literatura. O segundo capítulo foca nas modificações na biomassa, acumulação de níquel e aspectos morfofisiológicos de C. mucunoides e C. ensiformis em solos contaminados, revelando que C. ensiformis apresenta maior tolerância ao níquel, com adaptações anatômicas que permitem maior acúmulo do elemento. O terceiro capítulo examina as alterações na estrutura foliar dessas espécies sob estresse por níquel, utilizando análises morfológicas e bioquímicas para entender como as plantas mantêm a estabilidade celular e o funcionamento fisiológico frente ao estresse. O estudo mostrou que C. mucunoides apresenta maior sensibilidade, com alterações significativas na eficiência do uso de água e na atividade de pigmentos, enquanto C. ensiformis demonstra maior resistência, mantendo as trocas gasosas mesmo em condições de estresse elevado. As informações geradas contribuem para o conhecimento das estratégias de aclimatação das leguminosas tropicais a elementos potencialmente tóxicos, com implicações para o uso dessas espécies em programas de fitorremediação e recuperação de solos degradados.
Níquel em leguminosas tropicais: respostas de crescimento, impactos na morfofisiologia e perspectivas de sustentabilidade
Keywords: Nickel; Abiotic stress; Fabaceae; Tropical legumes; Phytoremediation; Morphophysiological acclimatization; Biochemistry; Níquel; Leguminosas tropicais; Estresse abiótico; Fitorremediação; Aclimatação morfofisiológica; Bioquímica